Unbalanced faults analysis in grid connected PV system / Listhianne Willy Anak Badi - Anak Badi, Listhianne Willy (2014)
One of the renewable energy found is solar energy where photovoltaic (PV) array is used to trap the energy from the sun and convert it to energy. PV is widely use in the grid -connected system nowadays. Since the founding of this method, the technology of extracting solar energy to photovoltaic array into grid network system has been growing rapidly. However, the existence of fault in the grid system may cause a drop in the outputs and will drop even lower with penetration of photovoltaic in the system. This work presents the effects of faults penetration inside the grid - connected PV system with three unbalanced faults being tested for this purpose and the results obtained will be compared to check which one contributes to high severity towards the grid - connected PV system. To observe the effects of these faults, a model of grid - connected PV system is built using MATLAB® 2009/Simulink with the help of Simscape and SimPowerSystems toolboxes. First, a PV system is developed in order to make the photovoltaic sourcing the system using a solar cell obtained from Simscape toolbox that then lumped with 70 others solar cell to make a PV module. With the help of a booster, the output voltage of PV system has increased and regulated and linked to a three - phase inverter circuit that successfully produced AC voltage. Stepped - up transformers then are placed at the end of the inverter to boost the AC voltage to values that shows the system modelled replicate that of real - life utility. Lastly, three faults are injected to Bus 1 consecutively and Bus 3 is observed for any changes in the phase voltage magnitudes and waveforms.